5-minute Marvel stories. (Los Angeles : Marvel Press, 2019)
"Join the most powerful heroes in the Marvel Universe as they team up to protect the world from the most dangerous foes imaginable. With special appearances from some of your favorite Marvel characters, each action-packed story is idea for reading aloud in just five minutes!" --
The new Spider-Man in town -- A family affair -- Journey to justice -- Attack of the portal crashers -- The switch up -- Full force! -- Rocket science -- Island of the cyborgs -- Iron Man: invincible! -- The hunt for Black Panther -- Mixed signals from Knowhere -- Ultron goes viral.
Keywords: Iron Man -- (Fictitious character) -- Juvenile fiction; Black Panther -- (Fictitious character) -- Juvenile fiction; Spider-Man -- (Fictitious character) -- Juvenile fiction; Superheroes -- Juvenile fiction; Supervillains -- Juvenile fiction; Good and evil -- Juvenile fiction; Adventure stories -- Juvenile literature; Science fiction -- Juvenile literature; Short stories -- Juvenile literature